Wage Growth Distribution and Changes over Time: 2001-2018 - Guyonne Kalb; Jordy Meekes (Institute of Labor Economics (IZA), 2020)
This paper investigates how wage growth varies among Australian employees with different individual characteristics and job characteristics, and how the role of these characteristics has changed over the 2001-2018 period. The results show that after increasing between 2002 and 2007, wage growth had significantly slowed down post 2008, and particularly from 2013 onwards, returning to the levels of the early 2000s. Employees' age, education, employment contract, occupation and industry explain a large share of differences in wage growth between individuals, and these characteristics are more important than aggregate business cycle effects. Conversely, the employee's gender seems less important. Interestingly, the employee's occupation is more important post-2008 than pre-2008, with managers and professionals experiencing substantially higher wage growth than others since 2014, whereas education was more important pre-2008. Finally, we find that casual employees receive a wage growth premium during the economic upturn and a penalty during the economic downturn.
Keywords: J31; J53; L24; 330; individual wage growth; aggregate wage growth; business cycle; wage differentials